Ingredient Awareness sebagai Pemicu Brand Switching dan Pergeseran Loyalitas Konsumen pada Industri Skincare di Era Transplantasi Digital: Systematic Literature Review - Handika Arif Setiawan; Nur Fasikha; Trio Nurcahya (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
Brand loyalty in Indonesia's skincare market, particularly among Generation Z and Millennial consumers, is undergoing a fundamental shift driven by increasing ingredient awareness, consumers' active knowledge and critical evaluation of active compounds in skincare products. This article examines this phenomenon through a Systematic Literature Review (SLR) of twelve articles from Scopus, Google Scholar, ScienceDirect, SpringerLink, DOAJ, and SINTA databases (2019–2026), following the PRISMA protocol. The study aims to: (1) analyze the direct influence of ingredient awareness on brand switching from global to local skincare brands; (2) examine the role of digital transparency as a moderating variable that amplifies this relationship; and (3) explain the mechanism of consumer loyalty transition in both generational segments. Thematic synthesis findings reveal that ingredient awareness drives brand switching through two cognitive pathways: post-awareness dissatisfaction and ingredient-driven variety seeking. Digital transparency ecosystems, comprising skinfluencer education on TikTok, cosmetic ingredient-scanning applications, and peer community reviews (e-WOM) act as accelerators converting cognitive awareness into actual brand-switching behavior. Cumulatively, a fundamental loyalty transition occurs from traditional brand loyalty toward functional ingredient loyalty. This article presents an integrative conceptual framework and four research propositions for future empirical validation. The findings also provide theoretical contributions to the consumer behavior and digital marketing literature by explaining how digitally mediated information ecosystems reshape loyalty formation in the skincare industry. Practically, the proposed framework may assist local skincare brands in developing ingredient-based communication strategies and transparency initiatives that strengthen consumer trust and long-term competitiveness in Indonesia's rapidly evolving beauty market.